Disentangling warning colouration : should aposematic individuals be conspicuous, distinct, or both? - Gilsenan, Carol (2012)
Aposematic species signal to potential predators of unprofitability due to their chemical defences by advertising one or a series of traits. Warning colouration is one such trait, and is a form of visual aposematism. Prey warning colouration is usually conspicuous in appearance, as it is believed that brighter and more obvious cues such as these make predator avoidance learning and memory more effective and longer lasting. However, the study of aposematism is confounded by the fact that initial evolution of conspicuousness in a prey population would have left those prey individuals at greater risk of being attacked by predators which had not yet learnt to associate the warning colouration with an unpalatable meal. In the past few years, studies have suggested that aposematism may instead have arisen through selection for distinctiveness (visual differences between the aposematic prey and other prey in the environment), rather than conspicuousness (visual differences between the aposematic prey and the background). For my Master of Science thesis, I sought to investigate this idea, using great tit (Parus major) predators, and a modification of the “Novel World” system. Both profitable and aposematic “prey” items were prepared, using small pieces of almond inside paper packages printed with either a cross or square symbol. These prey items were offered to birds on each of four backgrounds, namely white, cross, square, and mixed (cross and square) backgrounds, presenting a number of treatments in which prey items were conspicuous and/or distinct. The avoidance learning of the birds was measured over three trials. I found that prey distinctiveness alone was enough to deter the birds from unprofitable prey items, but prey conspicuousness also enhanced the avoidance learning process in some contexts. The results of the study suggest a role for both distinctiveness and conspicuousness in the efficacy of warning colouration, although their significance as an anti-predator strategy, especially that of conspicuousness, is most likely affected by both the particular environment and prey species composition. The development of warning colouration is therefore highly context-dependent, and should be discussed in future with respect to both conspicuousness and distinctiveness in the prey species, as both seem to play a part in aposematism.